The effect of playing and training surface on vertical jump height in elite junior male volleyball players: A pilot study - Crewe, A. (2006)
Many studies have considered the effect of training techniques (especially plyometric) on jump height. However, previous research has not considered the optimum surface for these training techniques. The aim of this research was to determine which training and/or playing surface is most beneficial in maximising vertical jump height for volleyball players. Attainment of such knowledge will not only assist athletes in optimising results but also help coaches in developing training. Conclusions. It is reasonable to suggest that sand training and playing surface had a greater effect on increasing vertical jump height on both surfaces.